FOSIL PROBOSCIDEA DARI SITUS SEMEDO: HUBUNGANNYA DENGAN BIOSTRATIGRAFI DAN KEHADIRAN MANUSIA DI JAWA - Siswanto; Sofwan Noerwidi (Berkala Arkeologi, 2014)
Semedo site is rich on vertebrate fossils, with huge percentage come from Ordo Proboscidea. The aim of this paper is to identify the taxonomy of Proboscidean fossils important for reconstruction on Biostratigraphy of Java. This research uses a descriptive comparative method on morphological and morphometry characters, compared to similar data from Java and others related places. Based on this research we know that in Semedo site there are several species of Proboscidean, i.e.: Sinomastodon bumiayuensis, Stegodon trigonocephalus, Stegodon â€pygmyâ€ semedoensis, Stegodon hypsilophus, Elephas (Archidiskodon) planifrons, and Elephas Hysudrindicus. This reflects that a long environmental changes or the history of ancient environment has been recorded in Semedo, related with ecological context of hominid appearance in this region.